Strategy Planning for The Development of The Penglipuran Tourism Village System using Togaf ADM - Nyoman Ayu Nila Dewi; riza wulandari (Universitas Trunojoyo Madura, 2022)
Denglipuran Tourism Village is one of the tourist destination on the island of Bali which is an attraction for tourists, but in managing business processes it has not made maximum use of the use of technology. This makes it difficult for the tourism management team to map and integrate business processes with technology. One of the impacts of not having a strategic planning document is like the current condition of the Covid-19 outbreak which has caused a decrease in the number of tourist visits coming to Penglipuran Village in addition to the decrease in the number of tour guides in the village. From these problems, the solution that is aimed in this research is to create a strategic planning document in the development of the Penglipuran tourism village system using Togaf ADM. This framework is used to align business processes with current technology. The next goal is to be able to provide strategic planning for the development of information systems that is clearly described, of course, by analyzing internal and external conditions. The results of the research that has been carried out have produced Togaf ADM artifacts, a blue print for system planning.